An introduction to ENSA: the animated screen annotation application / Farah Merican Isahak Merican, Syafiq Abdul Samat and Abdullah Kula Ismail - Isahak Merican, Farah Merican; Abdul Samat, Syafiq; Ismail, Abdullah Kula (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Kedah, 2022)
Lecturers and teachers had a drastic shift of teaching patterns when the COVID-19 pandemic happened. Face-to-face teaching has now moved to remote teaching; thus, making successful engagement and assessment more challenging. As they learn to observe and utilise the digital space, they consider new possibilities of teaching practices. Digital or screen annotation is one possibility that can transcend and assist the new normal in teaching. In traditional annotation, activities of note-taking, underlining, drawing, and highlighting are done on print-based texts (Kawase et al., 2009). Compared to screen annotation, all these activities can be done directly on screen-based texts (Dahl, 2016). In addition to that, screen annotation allows the insertion of recorded sound and videos (Olesh, 2016). This technology is a mix of presentation, screen capturing, whiteboard and note-taking tools (Tyrsina, 2021). It is an emerging educational technology and extensively used in education (Turner and Zucker, 2020). Screen annotation empowers lecturers and teachers to be more active and effective during lectures or classes. Besides that, the tools have been proven to significantly impact student engagement (Dahl, 2016 & Olesh, 2016). The usage of screen annotations in lectures have also resulted in strong positive feedbacks. Students place high value on the extra revision tools and work examples they get through screen annotated lectures (Rowlett et al., 2014). Another research done by Tseng (2021), also found that annotation tools foster better behaviour in student cognitive engagement. In addition, the same research concluded that annotation tools benefit and enhance student learning engagement (Tseng, 2021). Annotation process reassures active engagement, boosts critical thinking and promotes stronger retention in learning activities (Pearson, 2021)